Liver mitochondria-associated endoplasmic reticulum membrane proteomics for studying the effects of ZiBuPiYin recipe on Zucker diabetic fatty rats after chronic psychological stress - Xu, Huiying; Zhou, Wen; Zhan, Libin; Bi, Tingting; Lu, Xiaoguang (Frontiers in Cell and Developmental Biology, 2022)
Type 2 diabetes mellitus (T2DM) is a complex metabolic disease with multiple etiologies, involving both genetic and environmental factors. With changes associated with modern life, increasing attention has been paid to chronic psychological stressors such as work stress. Chronic psychological stress can induce or aggravate diabetes mellitus, and conversely, with the deterioration of T2DM, patients often experience different degrees of depression, anxiety, and other negative emotions. In order to clarify the role of ZiBuPiYin recipe (ZBPYR) in regulating the liver mitochondria-associated endoplasmic reticulum membrane proteome to improve T2DM with chronic psychological stress, differentially expressed proteins (DEPs) were identified among Zucker lean littermates (control group), chronic psychological stress T2DM rats (model group), and ZBPYR administration rats (ZBPYR group) through iTRAQ with LC-MS/MS. Using Mfuzz soft clustering analysis, DEPs were divided into six different clusters. Clusters 1-6 contained 5, 68, 44, 57, 28, and 32 DEPs, respectively. Given that ZBPYR can alleviate T2DM symptoms and affect exploratory behavior during T2DM with chronic psychological stress, we focused on the clusters with opposite expression trends between model:control and ZBPYR:model groups. We screened out the DEPs in clusters 1, 3, and 4, which may be good candidates for the prevention and treatment of T2DM with chronic psychological stress, and further conducted bioinformatics analyses. DEPs were mainly involved in the insulin signaling pathway, oxidative phosphorylation, tricarboxylic acid cycle, amino acid metabolism, lysosome-related processes, and lipid metabolism. This may indicate the pathogenic basis of T2DM with chronic psychological stress and the potential therapeutic mechanism of ZBPYR. In addition, two key proteins, lysosome-associated protein (Lamp2) and tricarboxylic acid cycle-related protein (Suclg1), may represent novel biomarkers for T2DM with chronic psychological stress and drug targets of ZBPYR. Western blot analyses also showed similar expression patterns of these two proteins in liver MAMs of the model and ZBPYR groups.